2001
DOI: 10.1161/01.res.88.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Alteration of Vascular Smooth Muscle Cells Precedes Elastolysis in a Mouse Model of Marfan Syndrome

Abstract: Abstract-Marfan syndrome is associated with early death due to aortic aneurysm. The condition is caused by mutations in the gene (FBN1) encoding fibrillin-1, a major constituent of extracellular microfibrils. Prior observations suggested that a deficiency of microfibrils causes failure of elastic fiber assembly during late fetal development. Mice homozygous for a targeted hypomorphic allele (mgR) of Fbn1 revealed a predictable sequence of abnormalities in the vessel wall including elastic fiber calcification, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
252
1
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 323 publications
(278 citation statements)
references
References 57 publications
18
252
1
7
Order By: Relevance
“…43 Electron microscopy showed that elastic laminae had an unusually smooth surface and lacked the cell attachments normally mediated by FBN1. 44 Bunton et al 44 suggested that the loss of cell attachments triggers signaling initiating a nonproductive program for the synthesis and remodeling of an elastic matrix. Thus, FBN1 appears to be a key element in the normal spatial organization of the arterial wall, ensuring adequate loading of elastic components, thereby maintaining physiological arterial stiffness.…”
Section: Marfan Syndromementioning
confidence: 99%
“…43 Electron microscopy showed that elastic laminae had an unusually smooth surface and lacked the cell attachments normally mediated by FBN1. 44 Bunton et al 44 suggested that the loss of cell attachments triggers signaling initiating a nonproductive program for the synthesis and remodeling of an elastic matrix. Thus, FBN1 appears to be a key element in the normal spatial organization of the arterial wall, ensuring adequate loading of elastic components, thereby maintaining physiological arterial stiffness.…”
Section: Marfan Syndromementioning
confidence: 99%
“…The so-called mgR mouse produces structurally normal fibrillin-1 protein at $15% of the normal level and in homozygosity replicates the adult lethal form of MFS (Pereira et al, 1999). Ruptured aortic aneurysm in mgR/mgR mice is preceded by a series of secondary events that include medial calcification, ECM accumulation, intimal hyperplasia, and adventitial inflammation (Pereira et al, 1999;Bunton et al, 2001). Overall, these secondary events suggested the activation of an unproductive tissue repair response, which results in intense elastolysis and consequent exacerbation of the structural collapse of the aortic wall (Pereira et al, 1999;Bunton et al, 2001).…”
Section: Fibrillins In Organ Development and Functionmentioning
confidence: 99%
“…Ruptured aortic aneurysm in mgR/mgR mice is preceded by a series of secondary events that include medial calcification, ECM accumulation, intimal hyperplasia, and adventitial inflammation (Pereira et al, 1999;Bunton et al, 2001). Overall, these secondary events suggested the activation of an unproductive tissue repair response, which results in intense elastolysis and consequent exacerbation of the structural collapse of the aortic wall (Pereira et al, 1999;Bunton et al, 2001). As already stated, subsequent studies of other fibrillin-1 mutant mice implicated enhanced TGF-b activity in initiating and/or maintaining pathogenic events in this mouse model of MFS.…”
Section: Fibrillins In Organ Development and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…19) In addition, inflammatory T lymphocytes and macrophages reportedly infiltrate aortic media and adventitia, and those numbers were negatively correlated with patient ages at referral for prophylactic surgical repair, suggesting that inflammation might affect disease progression. 20,21) Dietz and his colleagues performed the most extensive mechanistic studies of these diseases, and identified FBN1 as a causative gene in 1991, 4) with FBN1 mutations accounting for > 60% of MFS patients.…”
Section: Marfan Syndromementioning
confidence: 99%